ECCT: An Efficient-Cooperative ADHOC MAC for Cluster-Based TDMA System in VANETs - VanDung Nguyen; S. M. Ahsan Kazmi; Choong Seon Hong (International Journal of Distributed Sensor Networks)
In VANETs, a clustering algorithm can be used to partition the network into smaller segments. Therefore, the clustering algorithms provide not only limited channel contention but also fair channel access within the cluster. In addition, they also increase spatial reuse in VANETs and efficient control for the network topology. The main concern in the clustering algorithm is the cluster stability. The major challenge is to elect a cluster head and to maintain the membership of member nodes in a highly dynamic and a fast-changing topology. Therefore, the major criterion for cluster formation is to form a stable cluster. In this paper, a clustering algorithm to affect organization and cooperative ADHOC MAC for cluster-based TDMA system in VANETs (ECCT) is proposed. The cooperation is used to help a cluster head update each neighbor cluster's information which helps each cluster head to avoid collision when two clusters move into each other's cluster's transmission range. This efficiently utilizes a time slot. We use the lowest-ID algorithm to achieve organization. The analytical and simulated results show that not only the average number of time slots for electing a cluster head but also total number of time slots before data can be successfully transmitted is less than the existing cluster-based TDMA system and IEEE 802.11p.